2021
DOI: 10.3390/rs13030538
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Summer Diurnal Hot-Spot Analysis: The Role of Local Urban Features Layers

Abstract: This study was focused on the metropolitan area of Florence in Tuscany (Italy) with the aim of mapping and evaluating thermal summer diurnal hot- and cool-spots in relation to the features of greening, urban surfaces, and city morphology. The work was driven by Landsat 8 land surface temperature (LST) data related to 2015–2019 summer daytime periods. Hot-spot analysis was performed adopting Getis-Ord Gi* spatial statistics applied on mean summer LST datasets to obtain location and boundaries of hot- and cool-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…The shape index as an urban morphology element was also applied to each individual cool-and hot-spot feature, with the aim of providing a measurement of geometrical complexity of the hot-spot pattern. A recent study found that the shape index value of the extreme level was closely related to square or circular geometries, revealing that the highest average LST value of the study area was associated with a more regular shape than the corresponding cool-spot level [39].…”
Section: Introductionmentioning
confidence: 91%
“…The shape index as an urban morphology element was also applied to each individual cool-and hot-spot feature, with the aim of providing a measurement of geometrical complexity of the hot-spot pattern. A recent study found that the shape index value of the extreme level was closely related to square or circular geometries, revealing that the highest average LST value of the study area was associated with a more regular shape than the corresponding cool-spot level [39].…”
Section: Introductionmentioning
confidence: 91%
“…It avoids inconsistency in data collection processes, sensor types, and other meteorological factors [ 17 ]. In recent years, the rapid development of thermal infrared remote sensing technique has greatly promoted the diversification of remote sensing inversion methods for obtaining LST, such as Linear spectral mixture analysis (LSMA) model [ 18 , 19 ], single channel algorithm [ 20 ], atmospheric correction or radiative transfer method [ 21 , 22 , 23 ] and split-window algorithm [ 24 , 25 ]. In recent years, passive microwave (PMW) satellites have developed rapidly because of their ability to penetrate clouds, although PWM data suffer from lower spatial resolution and LST retrieval accuracy compared with thermal infrared data [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial clustering techniques are commonly used in the study of human geographic issues such as crime (Butt et al 2020 ). In recent times, however, these methods have been increasingly used in the analysis of physical geographic phenomena such as floods (Brandt et al 2020 ) and urban temperatures (Guerri et al 2021 ). Spatial clustering techniques use neighbourhood statistical measures to depict whether features with high (or low) values are clustered (or dispersed) together at a location, so space–time patterning can provide valuable insights into the management of highly localised atmospheric event like lightning.…”
Section: Introductionmentioning
confidence: 99%